Nano particles of Silicon effects on Photochemistry components (biological activity) and physiological properties of Coriandrum sativum plant under water stress - Alghamdi, Abdullah Musfer; Rashad, Hassan Mohammed; Algandaby, Mordi Mohammed (Journal of agricultural, environmental and veterinary sciences, 2024)
The present study was accomplished to scrutinize the efficiency of Nano silicon (NSi) as a foliar spray on (Coriander sativum) plants under water stress conditions during 2021/2022 season. Coriander plants were subjected to three water levels (100, 70 and 30% of field capacity). Plant leaves were sprayed with NSi in three different concentrations (3, 5 and 10 ppm) 14 days after germination. The results revealed that Coriander plants growth was significantly decreased under water stress, while NSi treatment showed a significantly enhanced plant growth (length and number of leaves per plant). Regarding biochemical constituents   activity, total of alkaloids, phenol, flavonoids and fatty acids increased under water stress. Also, nutrient elements (P & Mg and Na) increased. Plant hormones such as gibberellic acid (GA3) and ascorbic acid (vitamin C) significantly decreased under both 70% and 30% FC, while abscise acid (ABA) increased. In the interim, the three different concentrations of NSi significantly improved carbohydrates concentration and adjustment of osmotic stress. Application of NSi at different concentrations significantly improved nutrients contents (N, P, K, Mg, Ca, Fe, Zn, Mn) mainly under moderate and severe water stress (70%, 30% FC). Generally, the profound concentration of NSi tested during the experiment was 5 ppm for ameliorating water stress.   The present investigation showed that the application of NSi might be a promising method to enhance the plant growth, biochemical ingredients and crop productivity of Coriander plants grown under water stress conditions.
Keywords: Coriander plant; Nano; Silicon; Plant morphology; Biochemical ingredients; Water stress